Evolution of seed characters and of dispersal modes in Aizoaceae - Sukhorukov, Alexander P.; Nilova, Maya V.; Kushunina, Maria; Mazei, Yuri; Klak, Cornelia (Frontiers in Plant Science, 2023)
The family Aizoaceae includes ~1880 species and is one of the more diverse groups within Caryophyllales, particularly in arid areas in the western part of southern Africa. Most species are dwarf succulent-leaf shrubs. In response to the harsh climatic conditions prevalent where they occur, many representatives have evolved special reproductive adaptations. These include hygrochastic capsules (mostly found in Mesembryanthemoideae and Ruschioideae), burr-like indehiscent and one-seeded, winged diaspores, and fast germination of seeds after rain. We focused on anatomical features, evolutionary trends, and the ecological significance of various morphoanatomical structures found in the seeds. The seeds of 132 species from 61 genera were studied, and 18 diagnostic characters were discovered. All studied characters were compared with those of other families from core Caryophyllales. The seed notch and embryo shape were added to the list of characteristics distinguishing major clades within the family. In addition, the presence of longitudinal ridges and a keel on the seed are additional characters of Aizooideae and combined Ruschioideae-Apatesieae, respectively. Puzzle-like borders of testa cells are a common trait in Ruschioideae and Mesembryanthemoideae. Most taxa in Aizoaceae have a thin seed coat, which is the ancestral state within the family. This may facilitate fast germination. We observed several shifts to a medium-thick or thick seed coat in members of Ruschioideae and Acrosanthoideae. These inhabit fire-prone environments (in vegetation types known locally as fynbos and renosterveld), where the thickened seed coat may protect against damage by fire. Multiseeded fruits are the ancestral state within Aizoaceae, with several shifts to one-(two-)seeded xerochastic fruits. The latter are dispersed via autochory, zoochory, or anemochory. This trait has evolved mainly in less succulent subfamilies Acrosanthoideae, Aizooideae, and Sesuvioideae. In highly succulent subfamilies Ruschioideae and Mesembryanthemoideae, fruits are almost exclusively multiseeded and hygrochastic with ombrohydrochoric dispersal. A reduction in the number of seeds within a dispersal unit is rare. Within Apatesieae and Ruschieae, there are also a few unusual cases of genera because their fruits fall apart into one- to two-seeded mericarps (that are mainly dispersed by wind).